A biogeographical analysis of the polychaetes (Annelida: Polychaeta) from the gulf of Tehuantepec, México. - Solís-Weiss, Vivianne (2000)
The biogeographic affinities of 84 species of annelid polychaetes collected in the continental shelf of the Gulf of Tehuantepec are surveyed in this study. Four predominant faunistic assemblages were found: Wide distribution (24,99%), Amphiamerican (21,42%), Pacific (42,84%) and Disjunct (10,91%); those were defined from the eleven most generalized groups found there (Cosmopolitan, Circumtropical, Amphiamerican extended, Amphiamerican warm waters, Northeastern Pacific, Eastern tropical Pacific, Indopacific, Transpacific, Amphiamerican-Eastern Atlantic, Amphiamerican-Western Pacific, Eastern Pacific-Eastern Atlantic). The distribution patterns as well as the migration hypotheses that might explain the present distribution are discussed, and comparisons are made with recent biogeographic studies in nearby areas in the eastern Pacific such as Panama, Colombia and western Mexico.